2020
DOI: 10.1093/beheco/araa077
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone induces plumage ornamentation followed by enhanced territoriality in a female songbird

Abstract: We know little of the proximate mechanisms underlying the expression of signaling traits in female vertebrates. Across males, the expression of sexual and competitive traits, including ornamentation and aggressive behavior, is often mediated by testosterone. In the white-shouldered fairywren (Malurus alboscapulatus) of New Guinea, females of different subspecies differ in the presence or absence of white shoulder patches and melanic plumage, whereas males are uniformly ornamented. Previous work has shown that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 53 publications
4
26
0
Order By: Relevance
“…Higher concentrations of testosterone in M. a. moretoni females compared to M. a. lorentzi females is consistent with a role in coordinating expression of both plumage and behavior (Enbody et al, 2018). Moreover, Boersma et al (2020) were able to experimentally induce the white shoulder ornament in the population with unornamented females (M. a. lorentzi) via an exogenous testosterone implant. However, ornament expression in unornamented females is not a naturally occurring phenotype, and it remains unclear if androgens have an influence on ornament expression in populations with naturally occurring female ornamentation.…”
Section: Discussionsupporting
confidence: 63%
“…Higher concentrations of testosterone in M. a. moretoni females compared to M. a. lorentzi females is consistent with a role in coordinating expression of both plumage and behavior (Enbody et al, 2018). Moreover, Boersma et al (2020) were able to experimentally induce the white shoulder ornament in the population with unornamented females (M. a. lorentzi) via an exogenous testosterone implant. However, ornament expression in unornamented females is not a naturally occurring phenotype, and it remains unclear if androgens have an influence on ornament expression in populations with naturally occurring female ornamentation.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, female White-shouldered Fairywrens showed the opposite pattern by subspecies: lorentzi females had lower mean plasma testosterone than moretoni females in the previous study of testosterone in this species (Enbody et al, 2018). However, this has been attributed to variation in female ornamentation, as moretoni females exhibit male-like ornamentation, while lorentzi do not, although, they do produce some ornamentation when given exogenous testosterone (Boersma et al, 2020). In the current study lorentzi males were found to have higher circulating testosterone levels and greater social interaction scores, including interaction with more individual males and females and aggregating in display flocks (Figures 2 and 3), which is consistent with social interactions driving subspecific male testosterone levels.…”
Section: Discussionmentioning
confidence: 79%
“…For these reasons, testosterone has been referred to as a phenotypic integrator that regulates a network of traits (reviewed in Lipshutz et al 2019). While consequences of elevated testosterone circulation are reasonably well understood thanks to testosterone-implant studies (Boersma et al, 2020;Gerlach and Ketterson, 2013;Lindsay et al, 2011;McGlothlin et al, 2004;Peters, 2007;Peters et al, 2000;Peterson et al, 2013;Veiga et al, 2004;Zysling et al, 2006), the causes that lead to elevated endogenous levels in natural systems are more difficult to disentangle.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have suggested that female fairy-wrens are mechanistically constrained in their ability to produce black melanin-pigmented feathers. For example, Boersma et al (2020) found that some female White-shouldered Fairy-wrens of the subspecies lorentzi, which naturally lacks ornamentation, do not produce black feathers when supplied endogenous testosterone whereas others do. Similarly, Peters (2007) found that when treated with endogenous testosterone, female Superb Fairy-wrens Malurus cyaneus begin a prenuptial moult but the resulting feathers lack the blue and black structural coloration typical of males.…”
Section: Discussionmentioning
confidence: 99%